Detailed investigation of liquid distribution and holdup in periodic open cellular structures using computed tomography - Littwin, Giulia; von Beyer, Markus; Freund, Hannsjörg (Chemical Engineering and Processing, 2021)
Periodic open cellular structures (POCS) show great potential for process intensification in catalytic reactors due to their favorable properties regarding heat transfer, pressure drop and liquid distribution. In multiphase applications, POCS can be employed as multifunctional catalyst carrier with integrated liquid distribution function for enhancing the performance of heterogeneously catalyzed reactions. This applies particularly to trickle bed reactors where a uniform liquid distribution is of great importance. In this contribution, the liquid distribution of three POCS of different unit cell geometry is investigated using a custom-made computed tomography scanner with high spatial resolution. POCS with the Kelvin, diamond and DiaKel unit cell, respectively, were manufactured via fused deposition modeling out of acrylonitrile butadiene styrene. The liquid distribution was examined in dependence of the unit cell as well as for different liquid and gas flow rates. The three POCS show different behavior for the liquid distribution and holdup within the structures. POCS with Kelvin and DiaKel unit cell geometry show a higher liquid holdup as well as a more uniform liquid distribution compared to diamond unit cell POCS. Also, the liquid filling between the individual POCS that are stacked in the column is dependent on the unit cell.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Computed tomography; Liquid distribution; Liquid holdup; Multiphase system; POCS; Trickle bed reactor